Development and use of Ontologies Inside the Neuroscience Information Framework: A Practical Approach - Imam, Fahim T.; Larson, Stephen; Grethe, Jeffery S.; Gupta, Amarnath; Bandrowski, Anita; Martone, Maryann E. (Frontiers in Genetics, 2012)
An initiative of the NIH Blueprint for Neuroscience Research, the Neuroscience Information Framework (NIF) project involves advancing neuroscience by enabling discovery and access to public research data and tools worldwide through an open source, semantically enhanced search portal. One of the critical components for the overall NIF system, the NIF Standardized Ontologies (NIFSTD) provides a comprehensive collection of standard Neuroscience concepts along with their synonyms and relationships. The knowledge models defined in the NIFSTD ontologies enables an effective concept-based search over heterogeneous types of web-accessible information entities for the NIF's production system. NIFSTD covers major domains in neuroscience, including diseases, brain anatomy, cell types, subcellular anatomy, small molecules, techniques and resource descriptors. Since the first production release in 2008, NIF has grown significantly in content and functionality, particularly with respect to the ontologies and ontology-based services that drive the NIF system. We present here on the structure, design principles, community engagement and the current state of NIFSTD ontologies.